A novel synthesis method for MgB2 superconducting wires with kilometer-grade length. Issue 5 (1st April 2019) - Zhang, Wenjie; Zheng, Liang; Zou, Xiaofeng; Wang, Qi; Yu, Xuan; Yu, Zhou; Zhang, Hong; Zhao, Yong; Zhang, Yong
Abstract: We have successfully synthesized kilometer-length 6 + 1 filamentary MgB2 wires reinforced and toughened by Nb/Cu composite with in-situ powder-in-tube method, and for the first time innovatively applied the rapidly heating and quenching (RHQ) to the treatment of MgB2 wires, directly realizing the superconductivity of quenched MgB2 wires as well as the improvement of workability, thus avoiding the necessary annealing program in the conventional process. The results show that the phase composition of samples is mostly MgB2 after treatment with heating current at 350 A, except for a small amount of impurities. Most importantly, at 5 T and 20 K, the critical current density is still as high as 1.34 × 10 3 A cm −2, which fully meets the requirements of practical applications. This may be due to the relatively uniform distribution and compact MgB2 grains. This method is entirely possible to replace the traditional preparation technology and widen the market application prospect of MgB2 .